2006
DOI: 10.1653/0015-4040(2006)89[56:ehopch]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Egg Hatching of Periphyllus Californiensis (Hemiptera: Aphididae) in Two Microhabitats With Different Budburst Phenologies

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…For example, in the intestinal fluke of waterfowls Echinostoma caproni , it has been observed that eggs kept in darkness for up to 56 days do not hatch unless they are exposed to light [ 17 ], and frequency of egg-hatching increases with increasing light intensity [ 18 ]. In the maple aphid Periphyllus californiensis , eggs hatch much faster under shady sites than under sunny sites, because buds which the aphids feed upon open earlier in shady areas than sunny areas [ 19 ]. In the long-horned grasshopper Metrioptera hime , eggs hatch at higher rate under 12:12 hr LD compared to LL or DD [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the intestinal fluke of waterfowls Echinostoma caproni , it has been observed that eggs kept in darkness for up to 56 days do not hatch unless they are exposed to light [ 17 ], and frequency of egg-hatching increases with increasing light intensity [ 18 ]. In the maple aphid Periphyllus californiensis , eggs hatch much faster under shady sites than under sunny sites, because buds which the aphids feed upon open earlier in shady areas than sunny areas [ 19 ]. In the long-horned grasshopper Metrioptera hime , eggs hatch at higher rate under 12:12 hr LD compared to LL or DD [ 20 ].…”
Section: Introductionmentioning
confidence: 99%